1992
DOI: 10.1002/er.4440160907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the design variables on the energy performance and size parameters of a heat transformer based on the system acetone/H2/2-propanol

Abstract: A high‐temperature chemical heat pump based on the system acetone/H2/2‐propanol for waste heat recovery was studied. Two reversible catalytic chemical reactions are involved in this system. The waste heat (at 333–353 K) is recovered by means of the endothermic liquid‐phase dehydrogenation of 2‐propanol, and is upgraded at high temperature (453–473 K) by the reverse reaction, the exothermic gaseous‐phase hydrogenation of acetone. In this process, a fraction of the recovered waste heat is removed at low temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…Therefore, lower exothermic temperatures and higher endothermic temperatures were concluded as preferred for this type of organic CHP systems. However, this conclusion seems to be inconsistent with the previous results obtained by Saito et al [7] and Gandia and Montes [22]. Based on the catalytic dehydrogenation of alcohols at low temperature and hydrogenation of aldehydes or ketone at high temperature, Karaca et al [58] compared the economic costs for the organic CHPs employing methanol/formaldehyde/ hydrogen (M-F-H), ethanol/acetaldehyde/ hydrogen (E-AL-H), i-propanol/acetone/ hydrogen (iP-A-H), and n-butanol/butyraldehyde/hydrogen (nB-B-H) reaction systems.…”
Section: System Design and Evaluation Of Performance And Economycontrasting
confidence: 54%
See 2 more Smart Citations
“…Therefore, lower exothermic temperatures and higher endothermic temperatures were concluded as preferred for this type of organic CHP systems. However, this conclusion seems to be inconsistent with the previous results obtained by Saito et al [7] and Gandia and Montes [22]. Based on the catalytic dehydrogenation of alcohols at low temperature and hydrogenation of aldehydes or ketone at high temperature, Karaca et al [58] compared the economic costs for the organic CHPs employing methanol/formaldehyde/ hydrogen (M-F-H), ethanol/acetaldehyde/ hydrogen (E-AL-H), i-propanol/acetone/ hydrogen (iP-A-H), and n-butanol/butyraldehyde/hydrogen (nB-B-H) reaction systems.…”
Section: System Design and Evaluation Of Performance And Economycontrasting
confidence: 54%
“…The maximum exergy efficiency of 60 % together with the enthalpy efficiency of 21 % was obtained at T H = 543 K. Thus, it can be concluded that there is an optimal upgrading temperature (T H ) to acquire the maximum enthalpy efficiency and exergy efficiency. Nevertheless, the investigation conducted by Gandia and Montes [22] indicated a different conclusion, as depicted in Fig. 6.…”
Section: System Design and Evaluation Of Performance And Economymentioning
confidence: 72%
See 1 more Smart Citation
“…(1) and (2) constitute a closed cycle to convert low-temperature heat to high-temperature heat, and this cycle does not consume mechanical work. Gandia and Montes (1992) numerically investigate the IAH heat pump, in which the isopropanol dehydrogenation occurs in the liquid phase. Kim et al (1992) found that the dehydrogenation in the liquid phase can be improved by removing the gaseous acetone and the hydrogen products, and the enthalpy efficiency improves as the conversions of dehydrogenation and hydrogenation increase.…”
Section: Introductionmentioning
confidence: 99%
“…This endothermic reaction in the presence of a suitable catalyst required low-temperature heat is not thermodynamically favoured, due to its positive change of Gibbs free energy (Gandia and Montes, 1992). The chemical equilibrium can be shifted by evaporation of either of the products or both, i.e.…”
Section: Introductionmentioning
confidence: 99%